2021
DOI: 10.3389/fphar.2021.731499
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Host Defense Peptide (CaD23)-Antibiotic Interaction and Mechanism of Action: Insights From Experimental and Molecular Dynamics Simulations Studies

Abstract: Background/Aim: Host defense peptides (HDPs) have the potential to provide a novel solution to antimicrobial resistance (AMR) in view of their unique and broad-spectrum antimicrobial activities. We had recently developed a novel hybrid HDP based on LL-37 and human beta-defensin-2, named CaD23, which was shown to exhibit good in vivo antimicrobial efficacy against Staphylococcus aureus in a bacterial keratitis murine model. This study aimed to examine the potential CaD23-antibiotic synergism and the secondary s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Similarly, SYTOX Green (final concentration of 5 μM) ( 58 ) and propidium iodide (PI, final concentration of 10 μM) ( 8 ) were applied to evaluate the cell membrane integrity with excitation/emission wavelengths of 504 nm/523 nm and 535 nm/615 nm, respectively. In addition, the membrane potential was measured using 3,3-dipropylthiadicarbocyanine iodide (DiSC3[5], final concentration of 2 μM) ( 59 ) with an excitation/emission wavelength of 622 nm/670 nm with an interval of 5 min for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, SYTOX Green (final concentration of 5 μM) ( 58 ) and propidium iodide (PI, final concentration of 10 μM) ( 8 ) were applied to evaluate the cell membrane integrity with excitation/emission wavelengths of 504 nm/523 nm and 535 nm/615 nm, respectively. In addition, the membrane potential was measured using 3,3-dipropylthiadicarbocyanine iodide (DiSC3[5], final concentration of 2 μM) ( 59 ) with an excitation/emission wavelength of 622 nm/670 nm with an interval of 5 min for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Continuing on, our group has recently developed a library of novel bactericidal peptides through hybridisation of two different HDPs sequences, i.e., combining the benefits of two classes of HDPs into one molecule. A hybrid derivative of LL-37 and HBD-3, termed CaD23, was shown to enhance the potency of amikacin against Staphylococcus aureus [145,146]. Overall, antimicrobials targeting resistant pathogens will have their effect enhanced by HDP adjuvants and so reducing the effect of AMR.…”
Section: Use Of Hdps For Combat Against Antimicrobial Resistancementioning
confidence: 99%
“…Our group has fully characterised a range of HDPs on human corneal surface during disease and health [50,[68][69][70][71][72][183][184][185][186]. Recent studies from our laboratory showed that synthetic HDPs can be utilised for the treatment of Gram-positive and Gram-negative corneal infections [144][145][146].…”
Section: Other Applications Of Hdpsmentioning
confidence: 99%
“…11,12 Owing to the complex SAR and the costly and time-consuming process of wet-lab experiments associated with AMP investigations, many researchers have proposed computational approaches, including molecular dynamics (MD) simulations and machine learning (ML) algorithms, to accelerate the discovery and development of potential AMPs for clinical use. [13][14][15][16][17][18][19] Several studies have highlighted the promise of ML algorithms in predicting the antimicrobial activity, dissecting the complex SAR, and informing the drug design of AMPs. [13][14][15] A wide range of ML algorithms have been utilised, including random forests, 20 support vector machines (SVMs) [20][21][22][23][24] and articial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Several studies have highlighted the promise of ML algorithms in predicting the antimicrobial activity, dissecting the complex SAR, and informing the drug design of AMPs. [13][14][15] A wide range of ML algorithms have been utilised, including random forests, 20 support vector machines (SVMs) [20][21][22][23][24] and articial neural networks. [20][21][22]25,26 Many of these algorithms are used in combination with a carefully selected set of peptide features, which can be divided into two categories: compositional and physicochemical.…”
Section: Introductionmentioning
confidence: 99%